Paul and the Trinity persons, relations and the Pauline letters - Hill, Wesley, 1981- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2015)
Paul's way of speaking about God, Jesus, and the spirit are intricately intertwined talking about anyone of the three, for Paul, implies references to all of them together. However much current Pauline scholarship discusses Paul's God, Christ and spirit language without references to trinitarian theology. In contrast to that trend, Wesley, Hill argues in this book that later, post-Pauline Trinitarian theologies represent a better approach, opening a fresh angle on Paul's earlier talk about God the Father, Jeus Christ and the Spirit Hill looks critically at certain well-known discussions in the field of New Testament Studies--those by N.T. Wright, Richard Bauckham, Larry Hurtado and others--in light of patristic and contemporary trinitarian theologies, resulting in an innovative approach to an old set of questions. Adeptly integrating biblical exegesis and historical-systematic theology, Hill's Paul and the Trinity shows how trinitarian theologies illumine interpretive difficulties in a way that more recent theological concepts have failed to do.
Includes bibliographical references and indexes
Keywords: Bible. Epistles of Paul -- Criticism, interpretation, etc; Trinity -- Biblical teaching